Thermal degradation kinetics of polyesters containing mesogenic aromatic diols - Mule, Smita Atmaram; Ghadage, R. S.; Jacob, Nalini E.; Rajan, C. R.; Ponrathnam, Surendra (Journal Applied Polymer Science, 2005)
A series of polyesters were synthesized by reacting structurally differing aromatic diols with either saturated (flexible) or unsaturated (rigid) dicarboxylic acid halide by a stirred interfacial polycondensation technique. Thermal degradation kinetics of these polyesters were investigated by applying Coats-Redfern and Horowitz-Metzger nonisothermal procedures. The dynamic thermogravimetry experiments were conducted in nitrogen to obtain differential thermogravimetric plots. Thermal stability of these polyesters was discussed on the basis of semiquantitative methods such as differential procedural decomposition temperature, integral procedural decomposition temperature, and fraction decomposition temperature (e.g., 10 % DT). Degradation proceeded in multiple stages. The thermal degradation patterns and activation energies in these stages were discussed in relation to central bridging moieties of aromatic diol. The activation energies of these polyesters were found to be in the range of 100 to 200 kJ/mol. The effect of spacer type on activation energy was also reported. (c) 2005 Wiley Periodicals, Inc.
Keywords: Activation energy; Degradation; kinetics (polym.); Polycondensation; polyesters

Amino functionalized oligoimides telechelics - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Deokar, Sarika Babasaheb; Mulani, Khudbudin Baban; Ghorpade, Ravindra V.; Bhongale, Sunil Sitaram; et al. (2010)
This invention relates to a process for the preparation of amino functionalized oligoimide telechelics. More particularly it relates to a process for the preparation of soluble oligoimide prepolymers which can be used as matrix resins that can be rapidly cured to form stable polyimides with amino end functionalities. The amino functionalized oligoimide telechelics are suitable for conversion into three dimensional polymeric systems through condensation chemistry such as reaction with oligo epoxies (epoxy-imide resins), polyacids (polyamide imides) and polyhalogenated compounds (poly amine - imides) to form crosslinked structures having enhanced thermal stability and mechanical strength. The polymers prepared by the process of this invention can be used as materials in advanced composites having high temperature stability.

Amino functionalized oligo polyimides with enhanced storage stability - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Mohan, Srinivasulu Reddy Krishna; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Tayal, Rajiv Kumar; Shadbar, Qureshi Mohammed; Chavan, Nayaku; Deokar, Sarika Babasaheb; et al. (WO2012090055A1, 2012)
The invention relates to an improved process for the preparation of amino functionalized oligomeric monomeric reactant type polyimides having higher stability. More particularly it relates to a process for the preparation of soluble imide prepolymers, used as matrix resins that can be rapidly cured with multi-functional moieties such as diepoxy, dicarboxyl, anhydride, diisocyanates to form crosslinked structures having enhanced thermal stability and mechanical strength.

Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.